PERDAGANGAN ANAK (CHILD TRAFFICKING) LINTAS NEGARA DALAM KAJIAN HUKUM INTERNASIONAL - Zaenab Farhana; Chairul Bariah; Arif Arif (Journal of USU International Law, 2017)
ABSTRACTChild trafficking has long been happening on earth and is an act contrary to human dignity and prestige. This is a violation of human rights. In the past, child trafficking was only in the view of forcibly transferring abroad for the purpose of prostitution. But along with the times, trade is defined as transfers, especially children with or without the consent of the person concerned in a country or abroad for all exploitative labor, not just prostitution.   The type of research used in this study is normative juridical (legal research) that is by referring to various legal norms, in this case is international law and criminal law related to the sale of children across the country and the regulation of the prohibition.   The legal provisions governing the mediation of child trafficking are contained in the Convention on the Rights of the Child, namely article 35 which governs States to take national, bilateral and multilateral measures to interfere with the abduction, sale or trafficking of children for any purpose. This article does not provide a clearer explanation of child protection against child trafficking. The Convention on the Rights of the Child 1989 supplemented the Optional Protocol to the Convention on the Rights of the Child on the Sale of Children, Child Prostitution and Child Pornography set by the General Assembly of the United Nations on 25 May 2000. This Protocol aims to achieve the objectives of the Convention on the Rights of the Child and the application of further rules particularly those contained in articles 1, 11, 21, 32, 33, 34, 35 and 36.   Keywords: child trafficking, prevention, child rights